Vpliv hipoksije na vedenjsko termoregulacijo - poročilo z odprave Si.mobil Ski Everest 2000 - Mekjavić, Igor B. (Medicinski razgledi, 2002)
During the Si.mobil Ski Everest 2000 expedition the hypothesis that hypoxia affects temperature perception was tested. Subjects (N = 5), all members of the expedition, provided subjective ratings of temperature perception on a 7-point scale and thermal comfort on a 4-point scale at Base Camp (BC, 5360 m), Camp 1(C1, 6050 m), Camp 2 (C2, 6500 m), Camp 3 (C3, 7300 m) and Camp 4 (C4, 7950 m). In addition, we recorded oxygen saturation (SaO2, %), axilla temperature (Tax), and tympanic temperature (Tty). All measurements were made at 21.00 hrs after the subjects had been resting in a sleeping bag within the tent for a minimum of 30 minutes. Average (+- SD) SaOZ decreased from 75 (t 8)% at BC, to 65 (+- 5) % at C3. Although ambient temperature decreased with altitude from -9.6degreesC at BC to -27degreesC at C3, there were no sig nificant differences in either Tax šBCč 36.1 (+-0.1)degreesCč C1Č 35.7 (+-0.5)degreesCč C2Č 35.9 (t0.8)degreesCč C3Č 36.8 (+-0.8)degreesCđ or Tty šBCČ 36.9 (+-0.3)degreesCč C1Č 36.6 (+-0.5)degreesCč C2Č 36.8 (+-0.8)degreesCčC3Č 36.6 (+-0.8) degrees Cđ between measurements taken at the different camps. In contrast, there were significant changes (p < 0.001) in the perception of temperature from 4 (neutral) to 2 (cold) and in thermal comfort from 1(comfortable) to 3 (uncomfortable). All subjects reported experiencing an increased perception of warmth at the onset of supplemental oxygen breathing at altitude. Assuming that the subjectsć thermal status was similar during all measurements, we conclude that hypoxia alters the perception of temperature and thermal comfort.
Keywords: recreational mountaineering; gorništvo; nadmorska višina; hipoksija; mraz; telesna temperatura; termoregulacija; zaznavanje